2005
DOI: 10.1002/ajmg.b.30171
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of peripheral blood leukocytes from discordant sib-pairs with schizophrenia and bipolar disorder reveals points of convergence between genetic and functional genomic approaches

Abstract: We performed global RNA transcript analysis and comprehensive gene group analysis of peripheral blood leukocyte (PBL) RNA from two groups of matched sib-pairs that were discordant for either schizophrenia (n = 33 sib-pairs) or bipolar disorder (n = 5 sib-pairs). The pairs chosen for these analyses were selected from families with known patterns of genetic linkage (5q for schizophrenia and 6q for bipolar disorder). At the single gene level, we obtained lists of the transcripts with the most significant changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 15 publications
4
70
0
1
Order By: Relevance
“…KCNK1, a gene with a > twofold change in all three twin pairs and statistically significant differential expression in the microarray analysis, displayed a similar pattern of upregulation in all twin pairs by qRT-PCR, although the magnitude of the differences was smaller in each case. Likewise, the differentially increased expression of MAL, a gene identified in previous microarray studies, 6,34 was confirmed in all three twin pairs, although the increase in TP2 was only marginal (1.1-fold). The high fold-change differences between all three twin pairs for PFN2 determined by the array experiments (1.7-9.6-fold increased) were confirmed by qRT-PCR in all twin pairs except TP2, which showed no difference by qRT-PCR and had the lowest difference (1.7-fold) by microarray.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…KCNK1, a gene with a > twofold change in all three twin pairs and statistically significant differential expression in the microarray analysis, displayed a similar pattern of upregulation in all twin pairs by qRT-PCR, although the magnitude of the differences was smaller in each case. Likewise, the differentially increased expression of MAL, a gene identified in previous microarray studies, 6,34 was confirmed in all three twin pairs, although the increase in TP2 was only marginal (1.1-fold). The high fold-change differences between all three twin pairs for PFN2 determined by the array experiments (1.7-9.6-fold increased) were confirmed by qRT-PCR in all twin pairs except TP2, which showed no difference by qRT-PCR and had the lowest difference (1.7-fold) by microarray.…”
Section: Resultssupporting
confidence: 70%
“…40 Microarray studies assessing white blood cell-derived gene expression levels in BD1 have found, among many different processes, aberrations in RNA binding and ribosomal function, 6 as well as the ER stress response. 1 Similar work using OE has shown perturbations in phosphatidylinositol signalling, catecholamine metabolism, neurogenesis, apoptosis and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59,87 In those studies, the fold changes reported by the microarray and RT-PCR methods for the seven genes were highly correlated (r ¼ 0.95) based on triplicate assays for 19 sibpairs that had sufficient RNA for both procedures. In light of this previous work, and due to the limited amount of RNA available for validation in only a subset of the sample, we did not perform additional validation efforts in the present study.…”
Section: Genotypingmentioning
confidence: 96%
“…One group of biomarkers for neuropsychiatric disorders that shows considerable promise is blood gene expression profiling [108][109][110][111][112][113]. Most of the studies to date have focused on human lymphocytes gene expression profiling, comparison between illness groups and normal controls, and cross-matching with human postmortem brain gene expression data.…”
Section: Biomarkers For Autism Spectrum Disordersmentioning
confidence: 99%